Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease and Varicella Zoster Virus Infection - Frequency of an Association - Di Pauli, Franziska; Morschewsky, Paul; Berek, Klaus; Auer, Michael; Bauer, Angelika; Berger, Thomas; Bsteh, Gabriel; Rhomberg, Paul; Schanda, Kathrin; Zinganell, Anne; Deisenhammer, Florian; Reindl, Markus; et al. (Frontiers in Immunology, 2021)
To determine whether there is a correlation between myelin oligodendrocyte glycoprotein (MOG) antibody-associated diseases and varicella zoster virus (VZV) infection. We provide a case report and performed a study to determine the frequency of MOG antibodies (MOG-IgG) in neurological VZV infections. Patients admitted to the Medical University of Innsbruck from 2008–2020 with a diagnosis of a neurological manifestation of VZV infection (n=59) were included in this study; patients with neuroborreliosis (n=34) served as control group. MOG-IgG was detected using live cell-based assays. In addition, we performed a literature review focusing on MOG and aquaporin-4 (AQP4) antibodies and their association with VZV infection. Our case presented with VZV-associated longitudinally extensive transverse myelitis and had MOG-IgG at a titer of 1:1280. In the study, we did not detect MOG-IgG in any other patient neither in the VZV group (including 15 with VZV encephalitis/myelitis) nor in the neuroborreliosis group. In the review of the literature, 3 cases with MOG-IgG and additional 9 cases with AQP4 IgG associated disorders in association with a VZV infection were identified. MOG-IgG are rarely detected in patients with VZV infections associated with neurological diseases.